Design of a Fire Location Monitoring System Using Temperature and Smoke Detectors on Sea Ships - Rulaningtyas, S.T., M.T., Dr. Riries; Apriliyah, Indrawati; Winarno (Universitas Airlangga, 2022)
A fire location monitoring system is designed in this study to determine the location of a fire on a ship. The inputs used are temperature detectors and smoke detectors. The fire location monitoring system is designed using raspberry pi as a mini pc, temperature detector, smoke detector, alarm and Lazarus as a user interface. The room used as the object of research consists of the control room, steering room, engine room and kitchen room. The type and number of detectors used vary depending on the design of the detector placement in each room. Based on the tests that have been carried out, the fire location monitoring system is able to detect a fire when the temperature or smoke detector is active. In addition, the system is able to show the location of detectors that actively detect fires accompanied by an alarm sound. The average performance of the system in detecting a fire is 93%.